2021
DOI: 10.13057/biodiv/d220613
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study of plants used as food and for maternal health care by the Malays communities in Kampar Kiri Hulu, Riau, Indonesia

Abstract: Abstract. Susandarini R, Khasanah U, Rosalia N. 2021. Ethnobotanical study of plants used as food and for maternal health care by the Malays communities in Kampar Kiri Hulu, Riau, Indonesia. Biodiversitas 22: 3111-3120. Studies to reveal the diversity of food plants on communities living in remote areas with limited access to the market are important as an effort in documenting the traditional knowledge. The same applies to the diversity of medicinal plants used in maternal health care for communities that hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
2
17
0
2
Order By: Relevance
“…Moreover, several studies reported from other regions in the world such as Huai and Pei (2004) studied medicinal plants in the Lahu people from the Autonomous County of Jinping Miao, Yao, and Dai in southwest China, Gazzaneo et al (2005) studied in a region of Atlantic Forest in the state of Pernambuco (Northeastern Brazil), Chaudhary et al (2006) reported from Tian Mu Shan Biosphere Reserve, Zhejiang Province, China, Yineger et al (2008) studied in the Oromo ethnic group in southwestern Ethiopia, Supiadi et al (2019) studied the Dayak Desa Community in Sintang, West Kalimantan, Indonesia, and Susandarina et al (2021) studied in the Malays communities in Kampar Kiri Hulu, Riau, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies reported from other regions in the world such as Huai and Pei (2004) studied medicinal plants in the Lahu people from the Autonomous County of Jinping Miao, Yao, and Dai in southwest China, Gazzaneo et al (2005) studied in a region of Atlantic Forest in the state of Pernambuco (Northeastern Brazil), Chaudhary et al (2006) reported from Tian Mu Shan Biosphere Reserve, Zhejiang Province, China, Yineger et al (2008) studied in the Oromo ethnic group in southwestern Ethiopia, Supiadi et al (2019) studied the Dayak Desa Community in Sintang, West Kalimantan, Indonesia, and Susandarina et al (2021) studied in the Malays communities in Kampar Kiri Hulu, Riau, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Swingle "Lemon Lokal", C. × aurantiifolia "Jeruk Nipis"), childbirth treatment (C. × aurantiifolia), and other diseases. The use of C. aurantiifolia for childbirth treatment to ease labor in this province was also reported by Susandarini et al (2021). This species is also used to induce the production of breast milk.…”
Section: Traditional Treatment and Folklorementioning
confidence: 69%
“…The economic evaluation of edible plants in Muang District, Kalasin Province, was conducted between March 2019 and February 2021. Prices of edible plants (THB/kg) and the trading period were collected by the semi-structure interview method through an on-site survey and randomly informant selections in 13 local markets in Muang District (Numpulsuksant et al 2021;Saisor et al 2021;Susandarini et al 2021). In addition, the local name and edible plant specimens and their consumption methods (or their properties if the plants can be used for health treatments) were collected from trading sites, in natural (in case the edible plant was a natural product) and cultivation area.…”
Section: Study Conceptualmentioning
confidence: 99%